Al-Bīrūnī commemorative volume : proceedings of the International Congress held in Pakistan on the occasion of millenary of Abū Raihān Muhammad ibn Ahmad al-Bīrūnī 973-ca 1051 A.D., November 26, 1973 thru’ December 12, 1973 (Karachi)
844 s.